2015
DOI: 10.2174/1871530314666141128115225
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Controls Adipose Tissue Inflammation Associated with High- Fat Diet-Induced Obesity in Mice

Abstract: Our results suggest that drugs that can modulate the inflammatory status as well as control adipose tissue expansion could represent an interesting approach in the management of obesity, highlighting the need for further development of such compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In obese mice, chronic thalidomide treatment was reported to decrease MCP-1 expression and macrophages infiltration in adipose tissue41. It has been reported that high serum ICAM-1 level is associated with high mortality in cirrhotic patients42.…”
Section: Discussionmentioning
confidence: 99%
“…In obese mice, chronic thalidomide treatment was reported to decrease MCP-1 expression and macrophages infiltration in adipose tissue41. It has been reported that high serum ICAM-1 level is associated with high mortality in cirrhotic patients42.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have shown an effect of immunomodulation on adipose inflammation. ATM content and adipose tissue expression of inflammatory cytokines was lower in mice treated with methotrexate in 1 study , and the TNF inhibitor thalidomide in a separate study . These effects were also observed in obese mice treated with an MCP‐1 inhibitor .…”
Section: Discussionmentioning
confidence: 79%
“…This report suggested that thalidomide may reduce adipose tissue growth with reduced angiogenesis and inhibited preadipocyte differentiation, similar to a VEGFR-2 blocking antibody. In a recent report [14], thalidomide administration to high-fat diet-fed mice reduced visceral fat pad mass and adipocyte size. These results appear to agree with ours, although the dose of thalidomide and the treatment duration were different.…”
Section: Discussionmentioning
confidence: 99%
“…These results appear to agree with ours, although the dose of thalidomide and the treatment duration were different. The mechanism of the reduction of the visceral fat pad mass and of the adipocyte size in thalidomide-treated high-fat diet-fed mice may result from the immunosuppressive action of thalidomide [14]. The accumulation of intramyocellular lipid triglycerides is an important aspect of the insulin resistance of skeletal muscle in obesity and type 2 diabetes mellitus [15].…”
Section: Discussionmentioning
confidence: 99%